ADDITIONAL LOAD FROM RADIAL MISALIGNMENT OF SHAFTS AT THEIR COUPLING - Sokolovski, Slavcho; Staneva, Nelly (Innovation in Woodworking Industry and Engineering design, 2016)
A methodology for determining of additional load of shafts from deformation due to radial misalignment at their coupling is proposed. Shafts connected with rigid compensating coupling with cross coulisse (Oldham coupling) and with sleeve coupling are considered. The shafts displacement due to the additional load is determined for two cases: when supports are considered as perfect solid and when supports are considered as flexible with a radial clearance in the bearing. The elastic deformation of coupling sleeve is determined.